2021
DOI: 10.1007/s00405-021-06870-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia, trismus and speech impairment following radiation-based treatment for advanced stage oropharyngeal carcinoma: a one-year prospective evaluation

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Only a few studies reported a relationship between OD and body composition or weight loss in oncological populations using different methods, challenging clean comparison with our results. [44][45][46] For the evaluation of the swallowing function, these studies did not perform any biomechanical measurements using VFSS or fiberoptic endoscopic evaluation of swallowing (FEES) nor dysphagia-specific patient-reported outcome measures, and only two studies evaluated pretreatment OD. 44,46 Additionally, the presence of OD was evaluated using investigator-reported dietary intake scales (Food Intake Level Scale and FOIS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies reported a relationship between OD and body composition or weight loss in oncological populations using different methods, challenging clean comparison with our results. [44][45][46] For the evaluation of the swallowing function, these studies did not perform any biomechanical measurements using VFSS or fiberoptic endoscopic evaluation of swallowing (FEES) nor dysphagia-specific patient-reported outcome measures, and only two studies evaluated pretreatment OD. 44,46 Additionally, the presence of OD was evaluated using investigator-reported dietary intake scales (Food Intake Level Scale and FOIS).…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] For the evaluation of the swallowing function, these studies did not perform any biomechanical measurements using VFSS or fiberoptic endoscopic evaluation of swallowing (FEES) nor dysphagia-specific patient-reported outcome measures, and only two studies evaluated pretreatment OD. 44,46 Additionally, the presence of OD was evaluated using investigator-reported dietary intake scales (Food Intake Level Scale and FOIS). Previous research has shown that the FOIS or the level of dietary intake is not a reliable indicator for the severity of OD 47 so that the conclusions of the above-cited studies on the relationship between sarcopenia and OD should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low SMM was found to be predictive for length of hospital stay and unplanned admission in HNC patients treated with (chemo)radiotherapy ( 79 ). Low SMM was also associated with long-term morbidity of (chemo)radiation like dysphagia, xerostomia and trismus ( 40 , 80 , 81 ).…”
Section: Sarcopeniamentioning
confidence: 99%
“…Treatment of head and neck cancer (HNC) can affect the anatomy of the upper airway and upper digestive tract, often resulting in impairment of speech and swallowing function [ 10 , 11 ]. Another consequence of this altered anatomy is that it may lead to OSA [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%